2019
DOI: 10.1016/j.apmr.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Group Differences Among Caregivers of Civilians and Service Members or Veterans With Traumatic Brain Injury

Abstract: Objective: To examine group differences among caregivers of service members/veterans (SMVs) and civilians with traumatic brain injury (TBI). Design: An observational research study examining the group differences between caregivers of SMVs and civilians with TBI. The data presented was collected as part of a larger study that calibrated and validated the TBI-CareQOL item banks. Setting: Participants in this multicenter study completed an online survey via a study-specific website. Surveys were completed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Demographic, injury, and caregiving statistics are presented in Table 1. Due to substantial differences between caregivers of civilians and caregivers of SMVs on variables that could impact perceived sleep-related impairment and HRQOL, direct comparisons between these two samples were not made (Keatley et al, 2019). Instead, analyses were conducted in the combined sample and separately for the civilian and SMV groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic, injury, and caregiving statistics are presented in Table 1. Due to substantial differences between caregivers of civilians and caregivers of SMVs on variables that could impact perceived sleep-related impairment and HRQOL, direct comparisons between these two samples were not made (Keatley et al, 2019). Instead, analyses were conducted in the combined sample and separately for the civilian and SMV groups.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that caregiver perception of level of everyday function moderates social HRQOL for caregivers of SMVs and not caregivers of civilians warrants additional discussion. First, there are several differences between the two samples that may contribute to these discrepant findings between samples (Keatley et al, 2019). First, the SMV sample included mild TBI, whereas the civilian group did not, and there are several differences in demographic variables (highlighted in Table 1) that may contribute to differential findings.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in affective language have been found in several clinical populations, including individuals with right hemisphere brain damage ( 55 , 56 ), depressive disorder ( 57 ), schizophrenia ( 58 ), or ASD ( 59 ). Nevertheless, in clinical settings, the EWFT has only been used in studies with individuals with traumatic brain injury ( 60 ). Using the EWFT with healthy subjects, Abeare et al ( 61 ) found that trait anxiety was positively correlated with the number of emotions with negative valence produced.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of unpaid family or informal caregivers are performing medical/nursing tasks without training, and these caregivers report high levels of physical strain and emotional stress (National Alliance for Caregiving & AARP Public Policy Institute, 2015). In particular, caregivers of people with traumatic brain injury (TBI) have many unmet needs related to caregiving and coping (Adams & Dahdah, 2016; Moore, Kiatchai, Ayyagari, & Vavilala, 2017) and are at risk for poor health-related quality life (HRQOL; Carlozzi et al, 2015, 2016, 2018; Chan, Parmenter, & Stancliffe, 2009; Chronister, Chan, Sasson-Gelman, & Chiu, 2010; Griffin et al, 2017; Keatley et al, 2018; Kratz, Carlozzi, Brickell, & Sander, 2014; Lester et al, 2010; Mansfield et al, 2010; Phelan et al, 2011; Ruff, Ruff, & Wang, 2009; Saban et al, 2016; Taft, Schumm, Panuzio, & Proctor, 2008; Verhaeghe, Defloor, & Grypdonck, 2005). HRQOL is a multidimensional concept that includes physical, mental and social well-being (Fayers & Machin, 2007).…”
Section: Introductionmentioning
confidence: 99%